Archive as a Space of Identity: The Experience of Modern Ukrainian Literature - Романенко, Олена Віталіївна (Polish Academy of Sciences Chancellery, 2025)
This article analyzes the features of the archive as a memory space. The ideas of Aleida Assmans, Walter Benjamin, Susan Sontang, Sas Mays, and Anna Łebkowska constitute the intellectual support for the research. The research methodology is based on a combination of ideas from memory studies, postcolonial studies, and intermedia studies in the study of photography and its role within the artistic text. The works of modern Ukrainian literature represent the study material, in which the archive acts as a unique space that actualizes the mechanisms of recalling forgotten facts from family life or restoring historical individual memory. In such works, the archive acts as an object, a space of action, and an institution in which memories are accumulated, and the personal stories of the characters' identities are formed. Within collisions between “destruction of the archive vs. preservation of the archive” the plots of novels and stories about the identity of the characters and the ontological connections of time and space unfold. The article describes three leading models of depicting the archive as a space of memory: 1) the archive as a component of the identity of the individual and the identity of the nation (Valery Shevchuk’s novel Shadows are Gone (Тіні зникомі); 2) the archive and its components (for example, a photo) as a space of identity reconstruction (the novel by Oksana Zabuzhko The Museum of Abandoned Secrets (Музей покинутих секретів); 3) the archive as a destroyed space that inevitably transforms the identity of the individual (the novel by Pavlo Pastet Bedyanskyi Grandma Didn’t Like Dying (Бабуся не любила помирати). It has been proven that in artistic works the archive appears as a collection of objects (manuscripts, photos, etc.) and a space of memories (a collection of stories).
Keywords: chive; memory; novel; identity; Ukrainian literature; memory studies; intermedia studies